ANALYSIS AND EVALUATION OF CLASSROOM INTERACTION (VERBAL AND NON-VERBAL) AND TEACHING STYLE (DIRECT AND INDIRECT) IN PHYSICAL EDUCATION LESSON USING THE FLANDER SYSTEM FOR SYSTEMATIC OBSERVATION (Proximus Journal of Sports Science and Physical Education, 2024)
The goal of the study was to determine how objective observation might be a vital tool for examining teacher-student interactions. It also aimed to determine the kind of instruction used (direct or indirect), how much of each was used, and how each contributed to improving the learning process. The researcher postulated that the direct teaching style is more frequently employed by the research sample than the indirect style and that objective observation is a useful method for examining teaching behavior. Because it was appropriate for the type of research, the descriptive method with an analytical approach was used. There were seven female physical education teachers in the city of Samarra who made up the study population. Five teachers made up the final sample after the exploratory sample was purposely excluded to create the study sample. The Flanders Interaction Analysis System, which has a series of equations that may be used to extract different variables used in data processing, was employed by the researcher to measure classroom interaction. The research's main conclusions showed that when teaching facts, regulations, and sequential responsibilities in an orderly fashion, direct instruction is necessary. On the other hand, when teaching concepts and ideas using discoverybased methods, indirect teaching is used